Mycobacterium marinum: A Challenging Cause of Protracted Tenosynovitis - Pernille Grand Moestrup; Maiken Stilling; Christian Morberg Wejse; Victor Naestholt Dahl (MDPI AG, 2023)
Mycobacterium marinum infections are rare, and they can be difficult to diagnose and treat. This may lead to further spread of the infection and complications, such as tenosynovitis, pyomyositis, and osteomyelitis. A 40-year-old previously healthy man presented with tenosynovitis of the extensor tendons on the second phalanx of his right hand. He was initially treated with steroid injections without any effect. Followingly, ulceration and an abscess developed on the dorsal site of the hand. At this point, it came to the physician's knowledge that the patient had been cleaning an aquarium before onset of symptoms. After progression to massive tenosynovitis, the patient was admitted and underwent multiple surgical debridements. Briefly, after the first surgery, an interferon-γ release assay was positive, and treatment for M. marinum with rifampicin and azithromycin was initiated after eight months of symptoms. Later, a surgical biopsy showed acid-fast bacilli, and a polymerase chain reaction confirmed the diagnosis of M. marinum. In this case story, we highlight the difficulties of diagnosing and managing this complicated infection, describe the considerable morbidity associated with it, and suggest that local tissue concentrations could be useful to improve clinical outcomes, as these concentrations are potentially suboptimal.